Global Impact of Delayed Cord Clamping on Newborn Health: Dampak Global Penundaan Penjepitan Tali Pusat pada Kesehatan Bayi Baru Lahir - Muarofah Muarofah; Siti Cholifah; Paramitha Amelia Kusumawardani; Rafhani Rosyidahi (Academia Open, 2024)
Anemia and neonatal jaundice are major contributors to infant mortality. This study investigates the effects of delayed umbilical cord clamping on neonatal hemoglobin levels and jaundice. Using a quasi-experimental posttest-only control design, 101 newborns were sampled and divided into immediate clamping (<3 minutes) and delayed clamping (>3 minutes) groups. Hemoglobin levels were measured within 24 hours, and jaundice was assessed on days 4-7. Results showed that delayed clamping significantly increased hemoglobin levels (P = 0.000) and reduced jaundice incidence (P = 0.010). The findings suggest that delayed clamping improves early infant health outcomes and should be adopted in health facilities. Highlight: Delayed clamping improves hemoglobin, reduces jaundice in newborns. Quasi-experimental design compares immediate vs. delayed cord clamping effects. Adopting delayed clamping enhances early infant health outcomes. Keyword: Anemia, neonatal jaundice, delayed cord clamping, hemoglobin levels, infant health